Antibacterial Activity Test of Silver Nanoparticle Composites With Gandaria Seed (Bouea macrophylla G.) Bioreductor and Ouw Natural Clay Matrix (ONC) - Bijang, Catherina M.; Hasanela, Nurani; Joris, Shielda N.; Lihi, Risma; Salmawati, Mimi (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
An antibacterial activity test of silver nanoparticle composite with bioreductor of gandaria seeds (Bouea macrophylla G.) and Ouw natural clay (ONC) matrix was conducted. Silver nanoparticles (AgNPs) were synthesized by forming the colloidal silver solution by chemical reduction method using gandaria seed bioreductor. The formation of AgNPs can be known through UV-Vis absorption when there is a color change. Based on the results, the maximum wavelength of colloidal NPP is 435-444 nm. Silver nanoparticles synthesized through the preparation process were tested to determine their effectiveness as antibacterial agents against Escherichia coli and Staphylococcus aureus. The test results showed that the NPP formulation, containing an aqueous extract of gandaria seeds with the addition of polyvinyl alcohol (PVA), produced an inhibition zone of 10.6 mm against E. coli, indicating strong antibacterial activity. In contrast, the activity against S. aureus was classified as moderate, with an inhibition zone measuring 6.8 mm. For the antibacterial activity test with Ag/ONC nanocomposite samples on both test bacteria, there was no inhibition zone or antibacterial activity.